Internal mammary artery perforator-based V-Y advancement flap for the reconstruction of soft tissue defects in the sternal region. Issue 6 (December 2013) - Kim, Kwang Seog; Kim, Eui Sik; Hwang, Jae Ha; Lee, Sam Yong
Abstract: We successfully reconstructed a large defect that had been created by resection of an unstable, contracted, and hypertrophic scar with a chronic ulcer on the lower sternal area of a 67-year-old man. We used bilateral V-Y advancement flaps based on internal mammary artery perforators.